Using complete sentences and terms such as Suppose, consider, then, so, thus if necessary. Transcribed Image Text: 6.60. Below is given a proof of a result. Which result is being proved and which proof technique is being used?

Proof First observe that a = 8 = 3-1+5 and az = 11 = 3 – 2+5. Thus, an = 3n +5 for n = 1 and n = 2. Assume that a = 3i + 5 for all

integers i with 1* 2. Since k+1>3, it follows that
5ar – 4ak-1 – 9 = 5 (3k + 5) – 4 (3k +2) – 9
= 15k + 25 – 12k – 8 – 9 = 3k + 8 = 3 (k+1) +5.
ak+1*